Constraints of Applying e-learning in Secondary Schools Students’ Point of View: A field of study - Kadhim, Alaa (Al-Adab Journal, 2023)
The current research aims to find out the constraints of applying e-learning in secondary school students’ points of view in the Baladruz / Diyala Governorate. The field-survey approach was used to collect and analysis data via the SPSS program. The researcher selected the sample that consists 300 of 2001 the total of the population study from different variety schools in Baladruz city. An electronic questionnaire form consisted of 25 open-ended questions to measure the degree of constraints of applying e-learning from the point of view’s secondary school students. The research indicated that the degree of the constraints of applying e-learning from secondary school students’ point of view is large and real in the standard of the significant level of 0.082, as a result of human and material issues applying e-learning being faced effectively – and there is a statistically significant difference between Mean score in gender variable (M=males < females). It is recommended the necessity of providing and preparing schools in difference variety of digital technology tools and internet, technical laboratories to train learners and teachers on how to use ICT tools effectively in learning and teaching. It is suggested to study other variables.